2019
DOI: 10.18863/pgy.387288
|View full text |Cite
|
Sign up to set email alerts
|

Doğum Sonrası Depresyonda Bağlanma Örüntüleri ve Partner Desteğinin Rolü

Abstract: The birth of a baby, representing an important transition period in the lives of women, causes various changes and also brings about a great number of psychological problems in their lives. Postpartum depression is a highly prevalent disorder and previous research reveals that it is associated with several factors. Among these factors, the importance of partner relationship is especially highlighted and the variables that may affect this relationship negatively are one of the most important risk factors. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Accordingly, the mother's receiving both social, physical, and mental support from her partner, such as baby care, housework, and communication support, will enable her to carry out the postpartum period in a healthy way. When the literature is examined, it is reported that the support a woman receives from her husband during the postpartum period has a reducing effect on postpartum depression (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the mother's receiving both social, physical, and mental support from her partner, such as baby care, housework, and communication support, will enable her to carry out the postpartum period in a healthy way. When the literature is examined, it is reported that the support a woman receives from her husband during the postpartum period has a reducing effect on postpartum depression (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…The spouse's support during these procedures may have a favorable effect on the maternal quality of life. This support can be given through participating in infant care, helping with housework, supporting the mother emotionally, and sharing, thus contributing positively to the improvement of the maternal quality of life (9,(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%